1990
DOI: 10.1155/1990/921345
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind, Placebo Controlled, Multicentre Study of the Efficacy And Safety of 5-Aminosalicylic Acid Tablets in the Treatment of Ulcerative Colitis

Abstract: This double-blind, placebo controlled, multicentre, parallel trial assessed the efficacy of two oral doses of a new formulation of 5-aminosalicylic acid (5-ASA) targeted to release in the cecum which was given for six weeks to 136 patients with active ulcerative colitis. Seven centres participated (two Canadian, five American). Patients were randomly assigned to one of three treatment groups (4 g 5-ASA, 2 g 5-ASA or placebo). Medication was dispensed as 250 mg identically appearing tablets containing either 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 6 publications
1
29
0
Order By: Relevance
“…Schroeder et al13 demonstrated that a higher dose of the pH-dependent release formulation of 4.8 g/day showed greater efficacy than a dose of 1.6 g/day. In addition, when another formulation of pH-dependent release mesalamine (Rowasa) was administered to patients with active UC, UC-DAI after six weeks of treatment decreased from 8.5 to 4.8 at the 4 g/day dose, from 9.0 to 7.7 at the 2 g/day dose, and from 8.2 to 7.7 in the placebo group 14. In this report, we also showed that the pH-dependent release formulation at a higher dose significantly decreased UC-DAI (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Schroeder et al13 demonstrated that a higher dose of the pH-dependent release formulation of 4.8 g/day showed greater efficacy than a dose of 1.6 g/day. In addition, when another formulation of pH-dependent release mesalamine (Rowasa) was administered to patients with active UC, UC-DAI after six weeks of treatment decreased from 8.5 to 4.8 at the 4 g/day dose, from 9.0 to 7.7 at the 2 g/day dose, and from 8.2 to 7.7 in the placebo group 14. In this report, we also showed that the pH-dependent release formulation at a higher dose significantly decreased UC-DAI (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…However, this difference was due to the studies performed exclusively in USA, and it disappeared after those studies were omitted from the analysis. [85] and Australia [86] and one carried out jointly in the USA and Canada [87]. Among the studies conducted exclusively in USA reporting data on improvement rate, the Mayo Clinic (Rochester, MN) participated in four [33,34,36,58], the University of Chicago participated in three [31,53,56], Mount Sinai School of Medicine (New York, NY) [56,57] and George Washington University (Washington D.C.) [54,55] participated in two RCTs each, and one RCT each was carried out partially or solely at the Massachusetts General Hospital Boston [33], University of Iowa [42] and Albert Einstein College of Medicine New York [59].…”
Section: Placebo Remission Ratementioning
confidence: 99%
“…1. ) Five studies 10,11,13,17,18 were excluded because they were either unavailable in full text format, used a low (Ͻ2 g/d) dose of 5-ASA, or they did not report the data required to perform the analysis. The Mesalamine Study Group trial 11 was excluded because the dosage of mesalamine used for the study was less than 2 g/day, in order to maximize the homogeneity of the studies in the metaanalyses.…”
Section: Resultsmentioning
confidence: 99%
“…Feurle et al 10 and Hetzel et al 13 used olsalazine and did not clearly differen-tiate between diarrhea caused by olsalazine versus lack of treatment effect. Sutherland et al 17 did not specify exactly how many patients left the study for lack of efficacy in each arm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation